Constructivist Learning Practices among Elementary Islamic Education Teachers in Jordan - Mustafeh, Intisar (Jordan Journal of Educational Sciences, 2016)
This study aimed to explore Islamic education teachers' constructivist learning practices and its relation with some variables. The sample of the study consisted of thirty teachers specialized in Islamic education (2015/2016). The researcher designed an observation instrument which consisted of (37) items to collect the data about constrctivist learning environment. The findings revealed that the constructivist learning practices of Islamic education teachers have not developed to a high level of practice, but they have achieved a moderate and low degree. Moreover, it was found that there is no relation between the prospect constructivist teaching practices and teachers' experience, gender or their academic qualifications. Some recommendations were derived